Modern Democracy and Political Leaders - V. P. Kirilenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The subject of the presented research is the transformation of political leader’s authority inside the global network society in modern democracy. Scientifi works and studies based on introduction of some analogies from quantum physics into political science are overviewed in the article. The main purpose of such analogies is to improve the quality of political processes analysis and policy predictions. The term “quantum democracy” is used by the authors in relation to the crisis of democracy, noting the high degree of elitism of modern politics. The waves of globalization are destroying traditional social and political institutions faster than new power structures responsible for an effective policy decisions formed in specifi  countries. Democratic leadership develops in accordance with global trends, creating a new type of economically legitimate positional dominance, developing “legitimate naming” in the modern world. Political leaders under modern democracy retained the ability to bring their decisions in life to the extent that these decisions meet the condition of the national political fi Limitation of the political leader’s authority by the laws of quantum processes put legitimacy depending on those positions that are poles of the political